Targeted - Hunter, Stephen, 1946- (Hunter, Stephen, 1946- Bob Lee Swagger novel., 2022)
"After being accused of reckless endangerment and forced to answer to the U.S. Congress, master sniper Bob Lee Swagger must protect political hostages in a once-in-a-lifetime standoff"--